Research on Mixed Data Rate and Format Transmission in WDM Networks - Li Li Li Li; Wei Jian-yi; Zhang Xiu-tai; Li Hong-an Li Hong-an (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2013)
To meet the growing data traffic demands in the telecommunication applications, the number of wavelengths is to be increased in a fiber-optic backbone of the telecommunication network. The exponential growth of internet services, transmission capacity is a tremendous challenge to networks.   Nowadays, 10 Gb/s transmission systems are being used for commercial applications.  At the same time, the non-linear effects such as FWM, SRS, XPM, SPM, and Dispersion are also increased, when the number of wavelengths passing through the single fiber is increased. The analysis of efficient modulation formats for   DWDM system and    long-haul transmission system, we go for various modulations for DWDM system. The maximum data rate for NRZ-OOK modulation format is 10 Gb/s. For RZ-OOK the maximum rate is 50 Gb/s.  Since RZ-OOK modulation uses twice the band width when compared to NRZ-OOK modulation. The modulation format is partially upgraded from OOK to PSK, the influence of OOK signals on the updated PSK signals must be considered when using multi-channel wavelength conversion. The PSK modulation is also analyzed.